2011
DOI: 10.1093/bja/aeq369
|View full text |Cite
|
Sign up to set email alerts
|

No regional difference in cisatracurium dose–response and time-course-of-action between patients in China and Bosnia

Abstract: Cisatracurium dose-response relationship and time-course-of-action were not influenced by geographic location. Thus, cisatracurium would not require dose adjustments between patients living in the two geographic locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Geographic location and race are known to influence the potency and duration of drug action. Dahaba et al [ 13 ] found a significant difference in rocuronium potency and duration of action among patients in three countries; however, they also showed that there was no difference between Chinese and Caucasians in the comparative dose-response and time-course of cisatracurium activity [ 14 ]. The differences between the EDs in our study and those from existing studies [ 11 12 ] could be based on whether nitrous oxide was used.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic location and race are known to influence the potency and duration of drug action. Dahaba et al [ 13 ] found a significant difference in rocuronium potency and duration of action among patients in three countries; however, they also showed that there was no difference between Chinese and Caucasians in the comparative dose-response and time-course of cisatracurium activity [ 14 ]. The differences between the EDs in our study and those from existing studies [ 11 12 ] could be based on whether nitrous oxide was used.…”
Section: Discussionmentioning
confidence: 99%
“…We had to change the infusion dose nearly every 15 min to maintain a constant degree of NMB. If other neuromuscular blocking agents such as rocuronium, atracurium, 7 or cisatracurium 25 were used, the degree of fluctuation might have been different.…”
Section: Discussionmentioning
confidence: 99%
“…No differences were found between the white race and the yellow race in the effect of cisatracurium in the doseresponse and time-course-of-action relationships. 32 The autosomal-recessive deficiency of plasma cholinesterase, the enzyme necessary for the degradation of succinylcholine and mivacurium occurs most commonly in the population of white Europeans, while being virtually non-existent in sub-Saharan populations and in the yellow race. 6,33 The deficiency may lead to prolonged apnea after the administration of the agents mentioned above.…”
Section: Neuromuscular Blocking Agentsmentioning
confidence: 99%